In vitro anti-inflammatory activity among probiotic Lactobacillus species isolated from fermented foods. (August 2018) - Devi, Sundru Manjulata; Kurrey, Nawneet K.; Halami, Prakash M.
Highlights: Probiotic L. paraplantarum MTCC 9483 adhered more to epithelial Caco-2 cells. Gene expression of anti-inflammatory cytokines was observed during probiotic treatment. The adhesion domain of Lactobacillus species might have evolved from Listeria species. Isolate MTCC 9483 effectively modulated induced conditions by its anti-inflammatory activity. Abstract: Probiotic bacteria have the ability to alter immune response conferring treatment to inflammatory diseases. In the current study, probiotic Lactobacillus strains were subjected to adhesion to epithelial Caco-2 cells. Subsequently, gene expression of pro-and anti-inflammatory genes were studied under three stimulation conditions (which includes LPS-challenge, stress induction and pathogens invasion). Herein, immunomodulatory activity of native Lactobacillus strains (n = 3) were compared to L. rhamnosus GG. The studied strains had down-regulated the gene expression of pro-inflammatory cytokines (CKs) (like TNF-α, IL-1α, IL-1β, IL-6 and IL-8) and up-regulated the anti-inflammatory CKs like TGFβ1, IL-4, and IL-10. Gene expression of TLR2 has also been noted. Strain-specific interactions were noticed during the different probiotic treatment. Further, phylogenetic dendrogram of mucin adhesion domain suggested the interaction of Lactobacillus and Listeria species, explaining competitive colonization and exclusion mechanism in an ecological niche. Overall, isolate L. paraplantarum MTCC 9483 has effectively modulated induced conditions by its anti-inflammatory activity.